the analysis of airport operational performance case study: Chiang mai international airport, Thailand - Sopadang A. (2017)
© IEOM Society International. The purpose of this study is to determine which of the airport has the best performance in term of the number of passengers processed, in order to improve the airport operational performance. Data envelopment analysis (DEA) was employed to assess the operational performance of 19 airports in Asean plus 3. The methodology reflected which factors that was significant and related to the operational performance of the airport. There were 5 inputs (Terminal size, Number of runways, Lengths of runways, Number of gates and Check-in desks) and 1 output (Passenger movement) was deliberated in this study. The result of this study had shown that there were some major airports that inefficiency operated, due to using inefficiency input. Chiang Mai International Airport was also inefficient. The paper has done slightly further on sensitivity analysis, in order to evaluate the input-output of Chiang Mai International Airport. It presented that each time the input factors have changed, it made an impact to the efficiency score. The information of this study could support the Airports of Thailand to make decision about the future of Chiang Mai International Airport. © IEOM Society International.